Quantitative analysis of polyphenolic compounds in two different cultivars of marigold (Tagetes erecta L.) using high-performance thin-layer chromatography - Mir, Rayees Ahmad; Irshad, Saba; Argal, Surendra; Agarwal, Rajiv Mohan; Khatoon, Sayyada (Frontiers in Horticulture, 2023)
Marigold (Tagetes erecta L.) a popular ornamental plant of family Asteraceae is commonly cultivated in many countries including India for its decorative flowers. They grow easily in a variety of soil and climatic conditions and have been reported to damage the nematode population of soil and control indirectly harmful microbes. High Performance Thin Layer Chromatography was utilized for the present study with a view to identify some important biologically active compounds in the flowers and leaves of two different cultivars: Pusa Narangi Gainda (PNG) and Pusa Basanti Gainda (PBG) of marigold. The quantitative analysis were carried out using silica gel TLC plates and mobile phase used was toluene-ethyl acetate-formic acid (T-E-F) (13:11:2 v/v/v). Bands of gallic acid, caffeic acid, quercetin, p-coumaric acid and kaempferol were observed. Results revealed more compounds in leaves as compared to flowers and the cultivar PNG accumulated greater number of compounds than PBG. Gallic acid was found in leaves and flowers of both cultivars however, it was found maximum in the flowers of cultivar PBG. Caffeic acid and quercetin were detected in the leaves of both the cultivars whereas, p-coumaric acid was detected only in the leaves and kaempferol in the flowers of cultivar PNG. The information generated in this report may be meaningfully used for the furtherance of research on marigold as natural source of antioxidants, insecticides, herbicides etc.